Retention and teacher rotation in Municipal Education Networks in Brazil (Práxis Educativa, 2018)
This paper analyzes the retention and rotation rates of the Basic Education teachers in the Municipal Education networks in Brazil related to the period 2015-2016. These measures were operationalized based on the microdata of the School Census, considering the inflows and outflows of teachers, from one year to the next, in the educational establishments administratively linked to the municipalities. In addition to the results of retention and rotation rates of all municipalities in the country, the characteristics of the teachers (gender, color/race, Basic Education stage, type of hiring and location of the school) were presented. Keywords: Retention. Rotation. Teachers. Municipal Education Networks.